2018
DOI: 10.1097/md.0000000000010477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arthrocentesis plus platelet-rich plasma and platelet-rich plasma alone in the treatment of temporomandibular joint osteoarthritis

Abstract: Although the research on using platelet-rich plasma (PRP) for temporomandibular joint osteoarthritis (TMJ-OA) has advanced, no unified standards exist for determining the joint use of arthrocentesis and the injection dose and frequency of PRP. This study aimed to compare the efficacy of 2 TMJ-OA treatment approaches, arthrocentesis plus platelet-rich plasma (A+PRP) and PRP alone, and attempted to provide another potential treatment option with a single injection of 2 mL of high-concentration and high-purity PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 26 publications
1
48
0
1
Order By: Relevance
“…Pain was measured by VAS (visual analogue scale) in all works evaluated. Statistically significant results in terms of pain improvement were highlighted in all works examined, except in Lin et al [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain was measured by VAS (visual analogue scale) in all works evaluated. Statistically significant results in terms of pain improvement were highlighted in all works examined, except in Lin et al [25].…”
Section: Resultsmentioning
confidence: 99%
“…In both studies of Kiliç et al (2015, 2016) PRP and arthrocentesis and PRP injection was compared with arthrocentesis alone (2015) and with HA arthocentesis [8,9]. In Lin et al PRP arthrocentesis was compared with PRP injection [25].…”
Section: Resultsmentioning
confidence: 99%
“…25 Lin et al compared the efficacy of 2 approaches -arthrocentesis plus PRP and PRP alone -and concluded that arthrocentesis plus PRP demonstrated superior improvement in the jaw range of motion <6 mm and pain when chewing foods. 26 Zotti et al presented a narrative review on the effects of arthrocentesis with PRP and PRP injections in the management of TMDs and compared them to those of arthrocentesis alone or with HA. They found encouraging results in terms of the effectiveness of the PRP therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Until today there has been no clear research results into which of the evaluated preparations is more effective in intraarticular injections. The inspiration to undertake this type of research in the past [23] were very encouraging results of own and other authors' research concerning the use of PRP I HA in orthopedic treatment [7,9,19,20,[24][25][26][27]. These authors emphasized the beneficial influence of PRP on the healing processes of bones, ligaments, joint capsule, and s-joint structures [9].…”
Section: Discussionmentioning
confidence: 99%